Cattaneo-Christov model for electrical magnetite micropoler Casson ferrofluid over a stretching/shrinking sheet using effective thermal conductivity model - Shah, Z. (2019)
Nanofluids are the key building block of nanoparticles. So in particular, the researchers got attention in the development of nanotechnology. The knowledge of heat transmission in magnetohydrodynamic nanofluid flows through diverse geometries is significant for heat exchangers design, transpiration, fiber coating, etc. Currently, the nanomaterial's are among the well-known tackles for refining the low thermal conductivity of working liquids. Naturally, magnetite (Fe3O4) nanoparticles move randomly within the base fluid. When transverse magnetic force is applied, the motion of nanofluid becomes uniform. With this instigation, a mathematical model is developed to examine the heat transmission performance of electrically conducting MHD flow of a Casson ferrofluid over a stretching sheet. Moreover, we have considered water as a base fluid in this work. The formulated model has been solved with homotopy analysis method (HAM) by using similarity variables. The impact of embedded parameters on velocity, micro-rotation velocity, and temperature profiles have been shown graphically and discussed in detail. Also the impact of embedded parameters on surface drag force and heat transfer rate have been shown through tables and discussed as well. Â© 2018 The Authors.